Online monitoring of oil film thickness of journal bearing in aviation fuel gear pump. (30th November 2022) - Wei, Shijie; Wang, Junru; Cui, Jian; Song, Shanshan; Li, Huacong; Fu, Jiangfeng
Highlights: The ultrasonic method is proposed to measure the dynamic oil film thickness of the journal bearing in an aviation fuel pump. The circumferential oil film thickness is measured by applying the resonance and complex models jointly. The measured result is verified by comparing it with the DHL simulation under different operating conditions. Abstract: As the key support of aviation fuel pumps, journal bearings are operated under extreme conditions of high temperature, high pressure and low viscosity media, therefore, the broken of the ultra-thin lubrication film is the main cause of lubrication failure and abnormal wear. However, the dynamic hydraulic lubrication (DHL) film is still blind due to the lack of non-destructive online monitoring techniques. This paper presents the study of ultrasonic-based measurement for the dynamic oil film thickness of fuel pump. The circumferential oil film thicknesses in a journal bearing are measured with the complex model and the resonance model, meanwhile, the minimum oil film thickness is extracted by fitting the measured points with the initial circle. Under varying operating conditions, the measured results are verified with classical DHL simulations, and the maximum relative error is shown to be lower than 15%.